2022
DOI: 10.3892/mmr.2022.12760
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of retinol binding protein 4 with obesity and associated chronic alterations (Review)

Abstract: Obesity is a multifactorial disease, defined as excessive fat deposition in adipose tissue. Adipose tissue is responsible for the production and secretion of numerous adipokines that induce metabolic disorders. Retinol-binding protein 4 (RBP4) is an adipokine that transports vitamin A or retinol in the blood. High levels of RBP4 are associated with development of metabolic disease, including obesity, insulin resistance (IR), metabolic syndrome, and type 2 diabetes (T2D). The present review summarizes the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 95 publications
1
24
0
Order By: Relevance
“…These findings indicated that RBP4 could be considered as a biomarker to predict the risk and severity of AIS. This might be because: (1) RBP4 promoted endothelial cell inflammation through the nuclear factor-kappaB (NF-κB)/nicotinamide adenine dinucleotide phosphate oxidase (NADPH) pathway (Flores-Cortez et al 2022); meanwhile, inflammation played an important role in the pathogenesis of AIS (Jin et al 2013). Thus,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicated that RBP4 could be considered as a biomarker to predict the risk and severity of AIS. This might be because: (1) RBP4 promoted endothelial cell inflammation through the nuclear factor-kappaB (NF-κB)/nicotinamide adenine dinucleotide phosphate oxidase (NADPH) pathway (Flores-Cortez et al 2022); meanwhile, inflammation played an important role in the pathogenesis of AIS (Jin et al 2013). Thus,…”
Section: Discussionmentioning
confidence: 99%
“…stress by reducing endothelial mitochondrial function (Liu et al 2014, Flores-Cortez et al 2022; meanwhile, oxidative stress could induce brain injury, which was related to the pathogenesis of AIS (Hu et al 2022, Pawluk et al 2022, so RBP4 might accelerate the occurrence and severity of AIS. However, it is necessary to further clarify the specific mechanism of RBP4 to promote the development and progression of AIS.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…RBP4 is a useful biomarker for diagnosing obesity and the prognosis of related diseases ( 40 ), while IDH2 affects brown adipose tissue thermogenesis ( 41 ). In this study, RBP4 and IDH2 were differentially expressed based on the RNA-seq data (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, RBP4 is now also recognised as an adipokine with several roles in metabolism including insulin regulation (Aigner and Datz, 2011;Nankam and Blueher, 2021;Flores-Cortez et al, 2022;Ji et al, 2022). It is secreted by the liver and adipocytes such that the increase in serum RBP4 in pups with time could be directly due to the increase in blubber adipocyte mass, and it may play other important roles in controlling the metabolism in pups as they accumulate extensive body stores in preparation for weaning.…”
Section: Vitamin and Hormone-binding Proteinsmentioning
confidence: 99%